2012
DOI: 10.1074/jbc.m112.356105
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Domains within the V-ATPase Accessory Subunit Ac45 Involved in V-ATPase Transport and Ca2+-dependent Exocytosis

Abstract: The vacuolar (H(+))-ATPase (V-ATPase) is crucial for maintenance of the acidic microenvironment in intracellular organelles, whereas its membrane-bound V(0)-sector is involved in Ca(2+)-dependent membrane fusion. In the secretory pathway, the V-ATPase is regulated by its type I transmembrane and V(0)-associated accessory subunit Ac45. To execute its function, the intact-Ac45 protein is proteolytically processed to cleaved-Ac45 thereby releasing its N-terminal domain. Here, we searched for the functional domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…V-ATPase accessory proteins are known to regulate V-ATPase activity (Jansen et al, 2010a; Jansen et al, 2008; Jansen et al, 2012), but these proteins could also have V-ATPase-independent functions. We took two approaches to test whether KV phenotypes in Atp6ap1b depleted embryos are linked to altered V-ATPase function.…”
Section: Resultsmentioning
confidence: 99%
“…V-ATPase accessory proteins are known to regulate V-ATPase activity (Jansen et al, 2010a; Jansen et al, 2008; Jansen et al, 2012), but these proteins could also have V-ATPase-independent functions. We took two approaches to test whether KV phenotypes in Atp6ap1b depleted embryos are linked to altered V-ATPase function.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, proteomics studies on purified SVs have also revealed the presence of ATP6AP1 (ATPase H + Transporting Accessory Protein 1, also known as Ac45) and ATP6AP2 (ATPase H + Transporting Accessory Protein 2, also known as the (pro)renin receptor/PRR) . Those two brain‐enriched trans‐membrane proteins are accessory components of the vATPase with some additional cellular functions—for example, ATP6AP1 is involved in the vATPase transport and exocytosis, and ATP6AP2 is reported to be essential for biogenesis of active vATPases . ATP6AP2 is also ideally posed to link vATPase to cell signaling, for example, the renin‐angiotensin system for regulating blood pressure and electrolyte balance, as well as Wnt signaling during embryo development .…”
Section: Mechanisms Of Sv (Re)acidificationmentioning
confidence: 99%
“…Of note, knock‐outs of the essential vATPase subunits are lethal, as well as of accessory subunit ATP6AP1, making the studies of these proteins difficult. If not lethal, a genetic perturbation of the vATPase subunits and accessory proteins ATP6AP1 and ATP6AP2 lead to inherited disorders …”
Section: Regulation Of the Vatpase Activity On The Synaptic Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ac45 (Atp6ap1), an accessory subunit of the V-ATPase complex, is a type I transmembrane protein associated with the V-ATPase membrane domain (V0) (Yang et al 2012). The domains located in the N-and C-terminal portions of the Ac45 protein direct its trafficking, V-ATPase recruitment and Ca2 + -dependent-regulated exocytosis (Jansen et al 2012). Recently, overexpression of an Ac45 cytoplasmic terminus deletion mutant in RAW264.7 cells resulted in a dramatic reduction in osteoclast-mediated bone resorption and alterations in the binding proximity of Ac45 with the V-ATPase V0 domain subunits a3, c″ and d (Yang et al 2012).…”
mentioning
confidence: 99%